2014
DOI: 10.1371/journal.pone.0105193
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Persistence of the TNF Antagonists in Rheumatoid Arthritis – A Population-Based Cohort Study

Abstract: ObjectiveTo compare persistence with tumor necrosis factor alpha (TNF) antagonists among rheumatoid arthritis patients in British Columbia. Treatment persistence has been suggested as a proxy for real-world therapeutic benefit and harm of treatments for chronic non-curable diseases, including rheumatoid arthritis. We hypothesized that the different pharmacological characteristics of infliximab, adalimumab and etanercept cause statistically and clinically significant differences in persistence.MethodsWe conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 46 publications
(38 reference statements)
2
18
0
1
Order By: Relevance
“…Patients did not need to complete the 180-day gap before the end of the 12month post-index period to be classified as discontinuing therapy. Use of a 180-day gap is consistent with other published studies [25][26][27][28] and unlike studies with shorter gaps, we did not use days' supply, rather time between prescriptions and administrations.…”
Section: Assessmentssupporting
confidence: 82%
“…Patients did not need to complete the 180-day gap before the end of the 12month post-index period to be classified as discontinuing therapy. Use of a 180-day gap is consistent with other published studies [25][26][27][28] and unlike studies with shorter gaps, we did not use days' supply, rather time between prescriptions and administrations.…”
Section: Assessmentssupporting
confidence: 82%
“…In the literature proportion of patients remaining on INF is higher (more than 70 % in RA group, over 60 % in AS and PsA patients), although it must be noted, that the treatment dosage was higher (5 mg/kg in spondyloarthropathies) [33,34]. Similar drug survival was observed in RA patients treated with three TNFα blockers in Fisher's and colleague's paper, though our data showed statistically significant differences between BD groups and treatment survival time was shorter [35]. Better survival with ETA compared to ADA was observed in the PsA patients (68.3 % vs. 51.9 %), though better efficacy was observed in INF and ETA groups [36].…”
Section: Discussionsupporting
confidence: 60%
“…Most studies are either from Europe [7][8][9][10][11][12][13][14][15][16] or North America, [17][18][19][20][21][22][23] while studies in Asian populations are scarce. Apart from two Korean studies, 24,25 one Japanese prospective cohort study was identified that analyzed patients who started biologic treatment with infliximab, etanercept, or tocilizumab.…”
Section: Introductionmentioning
confidence: 99%